In vitro characterization of neurite extension using induced pluripotent stem cells derived from lissencephaly patients with TUBA1A missense mutations. Issue 1 (December 2016) - Bamba, Yohei; Shofuda, Tomoko; Kato, Mitsuhiro; Pooh, Ritsuko; Tateishi, Yoko; Takanashi, Jun-ichi; Utsunomiya, Hidetsuna; Sumida, Miho; Kanematsu, Daisuke; Suemizu, Hiroshi; Higuchi, Yuichiro; Akamatsu, Wado; et al.
Abstract Background Lissencephaly, or smooth brain, is a severe congenital brain malformation that is thought to be associated with impaired neuronal migration during corticogenesis. However, the exact etiology of lissencephaly in humans remains unknown. Research on congenital diseases is limited by the shortage of clinically derived resources, especially for rare pediatric diseases. The research on lissencephaly is further limited because gyration in humans is more evolved than that in model animals such as mice. To overcome these limitations, we generated induced pluripotent stem cells (iPSCs) from the umbilical cord and peripheral blood of two lissencephaly patients with different clinical severities carrying alpha tubulin (TUBA1A ) missense mutations (Patient A, p.N329S; Patient B, p.R264C). Results Neural progenitor cells were generated from these iPSCs (iPSC-NPCs) using SMAD signaling inhibitors. These iPSC-NPCs expressedTUBA1A at much higher levels than undifferentiated iPSCs and, like fetal NPCs, readily differentiated into neurons. Using these lissencephaly iPSC-NPCs, we showed that the neurons derived from the iPSCs obtained from Patient A but not those obtained from Patient B showed abnormal neurite extension, which correlated with the pathological severity in the brains of the patients. Conclusion We established iPSCs derived from lissencephaly patients and successfully modeled one aspect of the pathogenesis of lissencephalyin vitro using iPSC-NPCs and iPSC-derived neurons. The iPSCs from patients with brain malformation diseases helped us understand the mechanism underlying rare diseases and human corticogenesis without the use of postmortem brains.